Clinical Significance of Abnormalities in Fetal Kidney Location or Number Diagnosed by Prenatal Ultrasound - Lihong He; Jing Zhao; Hongli Wang; Rong Wei; Yun Liu; Xiaoxia Zha; Chunguo Zhang (Clinical and Experimental Obstetrics & Gynecology)
Background: The abnormal position or number of fetal kidneys accounts for 15%–20% of congenital abnormalities in the fetus, often resulting in oligo amniotic fluid or no amniotic fluid, thus affecting the development of fetal lung and resulting in a significant increase in the perinatal mortality of children. Therefore, detailed prenatal examination and evaluation of fetal kidneys should be carried out. Methods: We retrospectively analyzed data on fetuses with abnormal kidney location or number, as diagnosed by prenatal ultrasound in our hospital from January 2014 to December 2021. And analysis of the image characteristics, combined with intracardiac and extracardiac malformations, abnormal appendage and pregnancy outcomes, and statistical analysis of the ratio of each type of combined intracardiac malformation, combined with extracardiac malformation, abnormal appendage and induced labor rate respectively. Results: (1) A total of 7953 fetal cases were systematically screened, of which 391 had an abnormal fetal kidney location or number. These included 50 cases of horseshoe kidney, 169 cases of pelvic ectopic kidney, 12 cases of crossed ectopic kidney, and 160 cases of renal absence. (2) The 391 fetuses included 35 cases with intracardiac malformation, 163 cases with extracardiac malformation, and 85 cases with abnormal appendages. (3) With regard to pregnancy outcomes, 324 fetuses were born healthy and showed no significant abnormalities up to 2 years after birth, whereas 67 pregnancies were terminated due to severe fetal malformations. (4) There was no statistical significance in the ratio of intracardiac malformations among the four groups of horseshoe kidney, pelvic ectopic kidney, crossed ectopic kidney, and renal absence (p > 0.05); there was statistical significance in the ratio of the four groups with extracardiac malformations (p < 0.05); there was statistical significance in the ratio of the four groups with abnormal appendage (p < 0.05). The ratio of induced labor rate of the four groups was compared, and the difference was statistically significant (p < 0.05). Conclusions: Detailed prenatal ultrasonography can accurately diagnose fetal kidney location or number abnormalities, as well as fetal complications such as intra- and extra-cardiac malformations and abnormal appendages, providing important imaging information for subsequent clinical and eugenic care.